Semiotika untuk Memahami Makna Arsitektur Ragam Hias - Sri Sunarti; Ikaputra (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) Universitas Kristen Duta Wacana Yogyakarta, 2021)
Title: Semiotics to Comprehend The Change in The Meaning of An Ornament Semiotics is the science of a sign that consists of the structure of the signifier and the signified. As a medium of communication, a sign serves as a stand of something else or represents an expression message from the maker or owner to another party (interpretant) to be able to read. (Peirce, 1986 as cited in Chandler, 2007). Ornamental architecture is a work of art as a sign that is a medium of communication to viewers or related parties, which contains meaning that is not yet known or understood. The unknown meaning is caused by several types (1. decoration of new creations; 2. historical breakdown; 3. transfer of context; 4. correction of meaning due to discrepancies). Given that ornamental architecture is a sign of a grammatical